2020
DOI: 10.21203/rs.3.rs-49974/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Morphological and Molecular Characterization of Sarcocystis Wenzeli in Chickens (Gallus gallus) in China

Abstract: Background: There has been considerable confusion concerning the number and classification of Sarcocystis spp. found in chickens. To date, no nucleotide sequences of Sarcocystis spp. from chickens have been provided in GenBank. The present study aimed to investigate the morphological and molecular characteristics of Sarcocystis spp. in chickens in China.Methods: Tissues from 33 chickens were collected in 2019. Sarcocysts were observed using light (LM) and transmission electron microscopy (TEM). Individual sarc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Sarcocystis cristata is a separate species from Sarcocystis sp. isolated from chicken and S. wenzeli, which are the same species, as stated by Pan et al [19]. The latter two species and five other congeners formed a recurrent group of species reported in several previous works [e.g.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Sarcocystis cristata is a separate species from Sarcocystis sp. isolated from chicken and S. wenzeli, which are the same species, as stated by Pan et al [19]. The latter two species and five other congeners formed a recurrent group of species reported in several previous works [e.g.…”
Section: Discussionsupporting
confidence: 76%
“…For Sarcocystis species using birds as intermediate hosts, the ITS1 region was the most conclusive locus to clearly separate the new species from its congeners, while other loci were scarcely variable to distinguish species, although all genetic markers supported the designation of the new species. Apparently, the ITS1 region is more sensitive to the genetic differences among species, as mentioned by Prakas et al [24] and Pan et al [19], who also found a similar utility of molecular analysis while studying S. fulicae in Fulica atra from Lithuania and S. wenzeli in G. gallus from China, respectively.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations